Penguatan Akhlak Disiplin Peserta Didik Melalui Sosialisasi Tertib Berlalu Lintas di SMK Ma’arif 1 Kebumen - Khanifiiyah, Lulu Lestari; Astuti, Astuti; Saputri, Elika; Nachroy, Faiq Ali; Khanifiiyah, Lulu Lestari Nurul; Fatimah, Siti; Chamidi, Agus Salim; Subkhan, Subkhan; Aminah, Kun (IAINU Kebumen, 2024)
This research was conducted at SMK Ma'arif 1 Kebumen, a school located in Bumirejo Village, sub-district. Kebumen, district. Kebumen. Most of the students at SMK Ma'arif 1 Kebumen use motorized vehicles. The condition of the traffic road to SMK Ma'arif 1 Kebumen has a high traffic volume because the school is located in the center of Kebumen city which creates a risk of accidents for students who use it. motor vehicles to school increased'. Therefore, PLP IAINU Kebumen at SMK Ma'arif 1 Kebumen held a socialization on